Contribution of scintigraphy and ultrasonography to the prediction of malignancy in thyroid nodules with indeterminate cytology - Rosário,Pedro Weslley (2010)
OBJECTIVE: To evaluate the contribution of 131I scintigraphy and ultrasonography to the prediction of malignancy in thyroid nodules with indeterminate cytology in euthyroid patients. SUBJECTS AND METHODS: The sample consisted of 102 patients with thyroid nodules, submitted to FNAC and presenting an indeterminate cytological diagnosis (follicular neoplasm). RESULTS: Malignancy was observed in 19/25 (76%) nodules with suspicious ultrasonographic characteristics versus 5/77 (6.5%) without suspicious findings. When 131I scintigraphy showed a cold or hot nodule, the chance of malignancy was 38.5% and 2.5%, respectively. This exam was inconclusive in 10% of the patients. CONCLUSIONS: Surgery is indicated when a thyroid nodule with indeterminate cytology exhibits suspicious ultrasonographic characteristics. Otherwise, 131I scintigraphy can exclude thyroidectomy when reveals uptake in the nodule, which is observed in half the cases.